Efektifas Prinsip Restorative Justice Terhadap Anak Sebagai Pelaku Tindak Pidana Oleh Unit Pelayanan Perempuan dan Anak Polda Jambi - Islah, Islah; Siregar, Nella Octaviany (Universitas Batanghari Jambi, 2025)
This study aims to evaluate the efficiency of implementing the principles of restorative justice for children who are perpetrators of criminal acts by the Women and Children Protection Unit (PPA) of the Jambi Regional Police. It also examines the challenges encountered by investigators and the strategies employed to overcome those obstacles during the investigation process. Using an empirical juridical approach, the study finds that restorative justice is particularly effective in handling minor criminal offenses such as light assault, threats, and group violence. The effectiveness is reflected in three main aspects: informal resolution of cases, active participation of perpetrators, victims, and the community, and prevention of reoffending behavior through reconciliation. Internal obstacles include limited understanding of diversion procedures among investigators and the lack of child-friendly facilities. Externally, prevailing punitive public attitudes and distrust toward non-litigation resolutions hinder the process. To address these issues, investigators distinguish between diversion and restorative justice, enhance internal capabilities through training, and collaborate with external institutions while engaging in public outreach